Becoming in the Age of Artificial Intelligence:: philosophical, ethical, and technological reflections - ALVES DIAS, ROBINSON (Revista Interface Tecnológica, 2025)
This article aims to analyze the concept of becoming (devenir) as a dynamic and creative process that permeates human existence, in light of philosophical, ethical, and technological reflections. The research adopts a theoretical approach through an interdisciplinary literature review, with emphasis on authors such as Nietzsche, Deleuze, Bergson, Heidegger, Harari, among others. It examines the transformations of becoming in contemporary times, especially in the face of the impact of artificial intelligence (AI) on human subjectivity, memory, identity, and autonomy. The findings indicate that AI can both expand human possibilities and threaten freedom, ethics, and sustainability, depending on how the technology is used. It is concluded that technological becoming requires a critical and integrative reflection that balances innovation with essential human values.
Keywords: becoming; artificial intelligence; science; technology; society